Only transesophageal echocardiography guided patent foramen ovale closure: A single-center experience - Wang, Su; Zhu, Ge; Liu, Zhang; Zhou, Jian; Zang, Wangfu (Frontiers in Surgery, 2022)
Background: An increasing number of studies have proved that patent foramen ovale (PFO) occlusion could reduce the incidence of recurrent stroke more than drug therapy alone under certain conditions. Which is the "best" guidance technique still remains to be discussed. Methods: A single center retrospective study enrolled 120 patients (mean age 52.51±14.29 years) who underwent PFO closure between April 2019 and March 2021. 87 patients (72.5%) had suffered cryptogenic stroke (CS) at least one time, and 24 patients (20%) had repetitive episodes of hemicrania unsourced. 65 patients were in the transesophageal echocardiography (TEE) guidance group (T-group), and the other 55 patients were in the angiographic guidance group (A-group). Results: There were no significant differences in crucial clinical characteristics between the two groups. In T-group, the procedural success rate was higher (100% vs. 92.7%, P=0.028), and the procedural time was shorter (23.15±13.87 vs. 25.75±7.19, P=0.001). No difference was detected in the procedural complication rate. Follow-up were performed at least 12 months. At 12 months, new atrial fibrillation occurred in 1 patient (1.5%) in the T-group and in 1 patient (1.8%) in the A-group (P=0.905). Residual shunt occurred in 1 patient (1.5%) in the T-group and in 3 patients (5.5%) in the A-group (P=0.236). Recurrent cerebral ischemia occurred in 2 patient (3.1%) in the T-group and in 2 patients (3.6%) in the A-group (P=0.865). Conclusions: The use of only intra-procedural TEE guidance for PFO closure is safe and effective. The whole procedure can be performed without fluoroscopy and contrast medium. The short and medium follow-up results are satisfactory, especially in the residual shunt.